2016
DOI: 10.1080/2162402x.2016.1196309
|View full text |Cite
|
Sign up to set email alerts
|

Interferon alpha bioactivity critically depends on Scavenger receptor class B type I function

Abstract: Scavenger receptor class B type I (SR-B1) binds pathogen-associated molecular patterns participating in the regulation of the inflammatory reaction but there is no information regarding potential interactions between SR-B1 and the interferon system. Herein, we report that SR-B1 ligands strongly regulate the transcriptional response to interferon α (IFNα) and enhance its antiviral and antitumor activity. This effect was mediated by the activation of TLR2 and TLR4 as it was annulled by the addition of anti-TLR2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…A conspicuous amount of literature dealing with preclinical and translational aspects of ICB-based immunotherapy has appeared in peer-reviewed journals after the publication of our latest Trial Watch on the same topic (March 2015). 3 Of this exceptionally abundant literature, we found of particular interest several works focusing on resistance mechanisms and potential strategies for circumventing them, including the work of: (1) Ghoneim and collaborators (from the St. Jude Children's Research Hospital, Memphis, TN, US), who identified an epigenetic reprogramming mechanism relying on de novo DNA methylation 78 that restricts T cell expansion and clonal diversity upon PD-1 blockade; 79 (2) Benci and colleagues (from the University of Pennsylvania, Philadelphia, PA, US), who characterized a type I and type II interferon (IFN)-driven [80][81][82] signaling pathway though which cancer cells overexpress ligands for multiple T-cell inhibitory receptors to exacerbate local immunosuppression; 83 (3) Gao and co-workers (from the University of Texas MD Anderson Cancer Center, Houston, TX, US), who demonstrated that defects in interferon gamma (IFNG) [84][85][86][87] signaling are associated with hyporesponsiveness to CTLA4 blockade in mouse tumors models 88 as well as in melanoma patients; 44 (4) De Henau et al (from the Memorial Sloan Kettering Cancer Center, New York, NY, US) and Kaneda et al…”
Section: Update On the Preclinical And Translational Literaturementioning
confidence: 99%
“…A conspicuous amount of literature dealing with preclinical and translational aspects of ICB-based immunotherapy has appeared in peer-reviewed journals after the publication of our latest Trial Watch on the same topic (March 2015). 3 Of this exceptionally abundant literature, we found of particular interest several works focusing on resistance mechanisms and potential strategies for circumventing them, including the work of: (1) Ghoneim and collaborators (from the St. Jude Children's Research Hospital, Memphis, TN, US), who identified an epigenetic reprogramming mechanism relying on de novo DNA methylation 78 that restricts T cell expansion and clonal diversity upon PD-1 blockade; 79 (2) Benci and colleagues (from the University of Pennsylvania, Philadelphia, PA, US), who characterized a type I and type II interferon (IFN)-driven [80][81][82] signaling pathway though which cancer cells overexpress ligands for multiple T-cell inhibitory receptors to exacerbate local immunosuppression; 83 (3) Gao and co-workers (from the University of Texas MD Anderson Cancer Center, Houston, TX, US), who demonstrated that defects in interferon gamma (IFNG) [84][85][86][87] signaling are associated with hyporesponsiveness to CTLA4 blockade in mouse tumors models 88 as well as in melanoma patients; 44 (4) De Henau et al (from the Memorial Sloan Kettering Cancer Center, New York, NY, US) and Kaneda et al…”
Section: Update On the Preclinical And Translational Literaturementioning
confidence: 99%
“…This antiviral effect was not observed upon expression of IFN-α alone or other potent proinflammatory cytokines such as IL-12. Virus elimination was not dependent on T, B, Natural Killer cells and was probably due to a phenomenon of intrinsic immunity mediated by intracellular antiviral proteins [77]. This complex system was exploited to design a novel anti-tumor strategy based on a system of selfinactivating AAVs.…”
Section: Sr-b1 An Adaptive Danger Receptor: Sr-b1 Agonists As Adjuvanmentioning
confidence: 99%
“…Interestingly, the signaling pathway involving SR-B1 was not induced by traditional TLR2 or TLR4 ligands, indicating an active role of SR-B1 in the signaling pathway. The potential of this novel SR-B1 activity was highlighted when L37, an SR-B1 ligand, was combined with interferon alpha (IFN-α) [77]. Sustained expression of IFN-α and L37pA in murine livers by adeno-associated viruses (AAVs) triggered a potent anti-AAV response that partially eliminated the adeno-associated genomes.…”
Section: Sr-b1 An Adaptive Danger Receptor: Sr-b1 Agonists As Adjuvanmentioning
confidence: 99%
See 2 more Smart Citations